A retrospective analysis of the burden and treatment patterns of esophageal cancer over one year in a tertiary healthcare institution in the Western Himalayan region - Mahlawat, Nidhi; Patiyal, Nitin; Vias, Poorva; Sood, Atal; Bhagra, Suruchi (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Esophageal cancer (EC) is a highly aggressive malignancy with a poor prognosis, particularly in advanced stages. By 2024, EC incidence is expected to increase by 63.5% over 2020. The objective of the study was to analyse the EC burden and treatment patterns in Dr. RPGMC, Kangra, Himachal Pradesh, Radiotherapy and Oncology Department, with a focus on palliative radiotherapy. Methods: A retrospective analysis of 83 patients treated at our institute between 2023 and 2024 for esophageal cancer (7.9% of all new cases). Patients received treatment in two groups: palliative (n=34) and radical (n=49). Analysis was done on demographic, histopathological, cancer staging, and treatment modalities data. Self-expandable metallic stent (SEMS) implantation, palliative chemotherapy, or radiotherapy were all considered forms of palliative care. It was evaluated if palliative radiotherapy improved dysphagia. Results: Almost 8% of all cancers were esophageal cancers. There were 30.1% women and 69.8% men, with an average age of 63.9±9.6 years. In 98% of cases, squamous cell carcinoma was found. Of the palliative patients, three had SEMS placement, nine had chemotherapy, and twenty-two had radiotherapy. Following radiotherapy, dysphagia improved in 63.6% of palliative cases, or 68% of cases. Alcohol consumption and smoking were prevalent among men (76%). Conclusions: The study highlights the burden of EC and the importance of tailored treatment strategies. While radical treatment remains the preferred approach, palliative care plays a crucial role in symptom management for advanced cases (alleviating dysphagia, improving QOL).